Managing depression in primary care: A meta-synthesis of qualitative and quantitative research from the UK to identify barriers and facilitators - Barley, Elizabeth A (BioMed Central, 2011)
BACKGROUND: Current management in primary care of depression, with or without comorbid physical illness, has been found to be suboptimal. We therefore conducted a systematic review to identify clinician perceived barriers to and facilitators for good depression care. METHODS: We conducted a systematic literature search to identify qualitative and quantitative studies published in the UK since 2000 of GPs' and practice nurses' attitudes to the management of depression. We used principles from meta-ethnography to identify common and refuted themes across studies. RESULTS: We identified 7 qualitative and 10 quantitative studies; none concerned depression and co-morbid physical illness of any kind. The studies of managing patients with a primary diagnosis of depression indicated that GPs and PNs are unsure of the exact nature of the relationship between mood and social problems and of their role in managing it. Among some clinicians, ambivalent attitudes to working with depressed people, a lack of confidence, the use of a limited number of management options and a belief that a diagnosis of depression is stigmatising complicate the management of depression. CONCLUSIONS: Detection and management of depression is considered complex. In particular, primary care clinicians need guidance to address the social needs of depressed patients. It is not known whether the same issues are important when managing depressed people with co-morbid physical illness.